Low Back Pain Patient Distribution in Malang's Secondary Referral Private Hospital: A Single-Center Study - Filberto Filberto; Abdul Azis; Istan Irmansyah Irsan; Andhika Yudistira (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
The number of occurrences of Low back pain (LBP) in patients, especially the elderly, who still doubt the results of a treatment or surgery. Our study aims to review and summarize the latest literature on the distribution of LBP patients who come to specialist doctors by looking at the purposes of referral and use of BPJS (Indonesian Health Insurance). This data provides an overview of the LBP roadmap in a secondary referral hospital. We took Medical Record data from all patients who came to the Specialist polyclinic at Lavalate Hospital Malang as a Type B Referral from 2018 – 2021 (n= 644). The incoming data is grouped based on Gender, Patient Origin, Medical Expense Guarantee, Designated Medical Specialist, and Medication. The study was conducted descriptively and processed with a statistical program. The majority of the number of patients who came were dominated by the age of 51 – 70 years (25%), with more women (68.3%) than men (31.7%). The most choices for patients with LBP came to Orthopedics Specialists and Neurologists who had the same number of patients, namely 239 patients (36.1%). Most of the patients who came to the specialist clinic received therapy (81.9%) with NSAIDs as the most choice (69.3%) as the choice of medication. Antispasmodic and antiepileptic were followed as the next most popular choice, but each specialty has its uniqueness in treating LBP patients.